The Economics of Natural Disasters - Kellenberg, Derek; Mobarak, A. Mushfiq (Annual Review of Resource Economics, 2011)
This review discusses the ways in which countries are affected by natural disasters, depending on their socioeconomic characteristics, their level of development, and their inherent levels of natural disaster risk. We also explore various aspects of ex ante disaster mitigation such as improvements in natural disaster risk information and natural disaster insurance markets, as well as ex post responses to natural disaster in the form of postdisaster aid and long-run growth prospects. By highlighting some of the recent findings in this literature, we synthesize what we know about the economics of natural disasters and identify research areas of interest for future work.